The State's Responsibility in Preserving Local Culture: A Constitutional Law Perspective on the Practice of Akapalumba Jarangk - Sahajuddin, Sahajuddin; Reza Amarta Prayoga; Ansaar, Ansaar; Hafid, Abdul; Sritimuryati, Sritimuryati; Sutisna, Entis (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
The state holds a fundamental responsibility to protect the human rights of its citizens, including the right to safety, as outlined in national constitutions and international law. Despite this, violations of these rights are often perpetrated by both state entities and non-state actors. This study aims to examine the state's role in safeguarding citizens' right to security, particularly in the context of human rights violations in Indonesia. Utilizing a normative juridical methodology that incorporates both statutory and case law analyzes, complemented by literature review, the research findings indicate that while national and international legal frameworks mandate the state to ensure citizen safety, actual implementation is inadequate. This is characterized by limited accountability and insufficient restitution for victims. Therefore, there is a pressing need for enhanced legal protection mechanisms and institutional reforms to ensure that the state's responsibilities are met and that the right to security is upheld as a fundamental aspect of human rights.